2008
DOI: 10.1038/ncpcardio1399
|View full text |Cite
|
Sign up to set email alerts
|

Adverse cardiovascular effects of air pollution

Abstract: Air pollution is increasingly recognized as an important and modifiable determinant of cardiovascular disease in urban communities. Acute exposure has been linked to a range of adverse cardiovascular events including hospital admissions with angina, myocardial infarction, and heart failure. Long-term exposure increases an individual's lifetime risk of death from coronary heart disease. The main arbiter of these adverse health effects seems to be combustion-derived nanoparticles that incorporate reactive organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
398
2
9

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 673 publications
(416 citation statements)
references
References 68 publications
7
398
2
9
Order By: Relevance
“…The estimated annual premature mortality due to air pollution by the World Health Organization reaches 0.8 million (Mills et al 2009; http://www.who.int/whr/ 2002/en/whr02_en.pdf, p. 69). Poloniecki et al (1997) have shown a direct association between events of acute myocardial infarction (MI) and previous day air pollution in London, England.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated annual premature mortality due to air pollution by the World Health Organization reaches 0.8 million (Mills et al 2009; http://www.who.int/whr/ 2002/en/whr02_en.pdf, p. 69). Poloniecki et al (1997) have shown a direct association between events of acute myocardial infarction (MI) and previous day air pollution in London, England.…”
Section: Introductionmentioning
confidence: 99%
“…The solid matter alters lung, cardiovascular, nervous system functions, resulting in vascular inflammation, vascular dysfunction, and increased oxidative stress [38][39][40][41]. Nrf2 participates in resistance to hyperoxia-induced lung injury, it is also important in the response of epithelial cells particle exposure.…”
Section: Cardiovascular Diseasesmentioning
confidence: 99%
“…Likewise, smaller particles including PM 2.5 have a higher influence in respiratory illness such as inflammation compared to larger particles (Nurul Anis Sofiah and Juliana, 2013;Mills et al, 2009). Fine particles exist in greater numbers with greater surface area than larger particles of the same mass.…”
Section: Factors Influencing the Concentration Of Tnf-α Among School mentioning
confidence: 99%